Etiology and clinical characteristics of symptomatic unilateral maxillary sinusitis: A review of 174 cases. Issue 8 (October 2015) - Troeltzsch, Matthias; Pache, Christoph; Troeltzsch, Markus; Kaeppler, Gabriele; Ehrenfeld, Michael; Otto, Sven; Probst, Florian
Abstract: The purpose of the study was to analyze the causative pathology associated with symptomatic unilateral maxillary sinusitis requiring surgical treatment. A retrospective review of all patients that have been treated surgically for unilateral symptomatic maxillary sinusitis between 2006 and 2013 at a single institution was performed. Demographic, anamnesis, clinical, radiological, microbiological and histological data were gathered and analyzed. The patients were allocated into groups depending on the underlying cause of the disease. Descriptive and inferential statistics were computed (level of significance: p  ≤ 0.05). The study sample was composed of 174 patients (72 female; 102 male) with a mean age of 52.7 years (SD 16.9). Most cases (130; 75%) were triggered by odontogenic pathology following dentoalveolar surgical interventions (83/130 patients; 64%). Other etiological factors for odontogenic unilateral sinusitis were periapical (23/130 cases; 18%) and periodontal pathology (13/130 cases; 10%). Rhinogenic factors for sinusitis were detected in 13 patients (7.5%) and dental implant-associated unilateral maxillary sinusitis was diagnosed in nine patients (5.2%). Four patients (2.3%) had undergone previous sinus augmentation surgery. A leading cause for the sinus infection could not be identified in 18 patients (10%) who all had a history of midfacial surgery. Medication-related osteonecrosis of the jaw (8) and squamous cell carcinoma (2) were incidental findings. There were no differences in the clinical appearance of the disease with respect to its etiology. Odontogenic causes for maxillary sinusitis must be considered especially in unilateral cases. Maxillary dental implants may induce symptomatic unilateral maxillary sinusitis.